Birds' egges: The visual guide to the eggs of over 500 bird species from around the world - Michael Walters (Dorling Kindersley, 1994)
The book is divided into two sections: non passerines (all order of birds except Passeriformes); and then passerines (birds of the order Passeriformes). Within these sections, the eggs are arranged in family groups. A full-color illustration shows a bird representative of the species, and color-coded bands on the bands of the page, give at-a-glance facts for quick reference. Finally, a concise glossary provides instant understanding of zoological terms